The Role of Medical Rehabilitation: Management of Oromotor Dysfunction (Mechanical and Kinetic Movement Dysfunction) and Speech Therapy in Children with Cerebral Palsy - Anak Agung Ayu Niti Wedayani; Nurul Ullyani; Novia Andansari Putri Restuningdyah; Linda Silvana Sari; Aris Doyan (Jurnal Penelitian Pendidikan IPA, 2024)
Cerebral palsy (CP) is a non-progressive motor disorder caused by prenatal, perinatal, and postnatal factors, leading to movement and posture abnormalities. In Indonesia, around 0.60% of the total child population has CP (9 cases per 1000 live births). Speech and swallowing difficulties are common, affecting children’s nutritional status and development. Speech and oral motor therapy are effective in improving speaking and oromotor dysfunction. To determine the effectiveness of oromotor and speech therapy in improving swallowing, chewing, and speech abilities in children with CP. A case study was conducted at the "Lombok Care" Children with Disabilities Foundation. Language development was assessed with the Messay Language Test, and oromotor dysfunction was evaluated using Debra C. Gangale’s method. Pre and post-therapy assessments were performed to assess changes in motor and speech functions. The evaluation of 5 respondents showed an increase in speaking skills after speech therapy and swallowing skills after oromotor therapy. Both are shown to be effective in improving communication skills and oropharyngeal muscle coordination, as well as reducing the risk of aspiration. Speech and oral motor therapy are essential and effective in improving eating, swallowing, and speaking abilities in children with CP, and are an important part of holistic medical rehabilitation.